Cather Studies, Volume 12 : Willa Cather and the Arts. - Studies, Cather (Cather studies., 2020)
"Informed by new modes of contextualization, including the increasingly popular view of Willa Cather as a pivotal or transitional figure working between and across very different cultural periods, and by the recent publication of Cather's correspondence, the essays in this collection reassess Cather's lifelong encounter with, and interpretation and reimagining of, the arts"--